Thismia nigricoronata, a new species of Burmanniaceae (Thismieae, Dioscoreales) from Vang Vieng, Vientiane Province, Laos, and a key to subgeneric classification - Kumar, Pankaj; Gale, Stephan W.; Li, Ji-Hong; Bouamanivong, Somsanith; Fischer, Gunter A. (Phytotaxa, 2017)
Thismia nigricoronata is described as a new species in family Burmanniaceae. Both morphological and phylogenetic analyses indicate that this new Lao endemic is allied to T. taiwanensis in section Glaziocharis, and it can be differentiated on the basis of its longer vestigial stem leaves, reflexed free outer perianth lobes and ornamented, vibrantly coloured outer surface of the perianth tube. The infrageneric taxonomy of Thismia is reviewed, the genera Geomitra and Scaphiophora are officially reduced to sectional status in Thismia, and all species are enumerated in systematic order. A key to all currently accepted subgenera, sections and subsections is presented to facilitate further examination of their phylogenetic integrity in light of apparent conflict between the traditional morphology-based system and the emerging DNA-based classification.